Konsentrasi Auditor dan Penetapan Fee Audit: Investigasi Pada BUMN - Michell Suharli; Nurlaelah Nurlaelah (Jurnal Akuntansi dan Auditing Indonesia, 2008)
This research is aimed to test the influence of auditor concentration ratio, KAP size, the size of company auditee and number of subsidiary company towards an audit fee. The samples of this research are 22 BUMN companies in periode 2002-2004. The data is taken from the annual report of companies. This study use linear regression which consists of two variables. The first is dependent variable this is audit fee. The second variable is independent variable consist of ratio concentration variable, KAP size, company auditee size and company subsidiary. The result of the study shows that there are two significant variables i.e. ratio concentration and company auditee size. More over, it is also found that there are two unsignificant variables namely KAP size and the number of subsidiary company.Keywords: Concentration Auditor, audit fee, auditing.